Blunt snout bream (Megalobrama amblycephala) MaCSF-1 contributes to proliferation, phagocytosis and immunoregulation of macrophages via MaCSF-1R. Issue 127 (August 2022) - Wang, Huabing; Zheng, Feifei; Ouyang, Aotian; Yuan, Gailing; Su, Jianguo; Liu, Xiaoling
Abstract: CSF-1 and CSF-1R have been well demonstrated in humans, regulating the differentiation, proliferation and survival of the mononuclear phagocyte system. However, the functional study on MaCSF-1 and MaCSF-1R from blunt snout bream ( Megalobrama amblycephala ) is still unknown. In the present study, we cloned and functionally characterized MaCSF-1 and MaCSF-1R. Multiple sequence alignment and phylogenetic tree analysis showed that both MaCSF-1 and MaCSF-1R were mostly close to the grass carp counterparts. Tissue distribution analysis showed that both MaCSF-1 and MaCSF-1R were widely distributed in all examined tissues, dominantly distributed in spleen, blood and head kidney tissues. Furthermore, confocal microscopy assay and flow cytometry assay showed that MaCSF-1R was the marker on the surface of macrophages. Recombinant MaCSF-1 promoted macrophage proliferation, phagocytosis and the production of IL-10. Through the pull-down experiments and indirect immunofluorescence experiments, the interaction between MaCSF-1 and MaCSF-1R was confirmed. To explore the relationship between MaCSF-1 and its receptor, MaCSF-1R and MaCSF-1R antibody was prepared. Then the MaCSF-1R blockage assay indicated that the role of MaCSF-1 on the macrophages proliferation and phagocytosis was weakened, leading the reduction of IL-10 expression level. In conclusion, MaCSF-1R is the marker on the surface of macrophage membrane; and MaCSF-1 promotes macrophage proliferation, phagocytosis, and significantly increased the expression levels of IL-10 depended on the interacting with MaCSF-1R. This study provides basal data for the biological function of MaCSF-1 and MaCSF-1R, and is valuable for the exploration of MaCSF-1 and MaCSF-1R molecular interactions. Highlights: MaCSF-1R is a surface marker of Megalobrama amblycephala macrophage. MaCSF-1 promotes macrophage proliferation, phagocytosis and production of IL-10. MaCSF-1 exerts the functions via MaCSF-1R.